Hypercholesterolemic Dysregulation of Calpain in Lymphatic Endothelial Cells Interferes With Regulatory T-Cell Stability and Trafficking. Issue 2 (15th December 2022) - Miyazaki, Takuro; Taketomi, Yoshitaka; Higashi, Takayoshi; Ohtaki, Hirokazu; Takaki, Takashi; Ohnishi, Koji; Hosonuma, Masahiro; Kono, Nozomu; Akasu, Risako; Haraguchi, Shogo; Kim-Kaneyama, Joo-Ri; Otsu, Kinya; et al.
Abstract : Background: Although hypercholesterolemia reportedly counteracts lymphocyte trafficking across lymphatic vessels, the roles of lymphatic endothelial cells (LECs) in the lymphocyte regulations remain unclear. Previous studies showed that calpain—an intracellular modulatory protease—interferes with leukocyte dynamics in the blood microcirculation and is associated with hypercholesterolemic dysfunction in vascular endothelial cells. Methods: This study investigated whether the calpain systems in LECs associate with the LEC-lymphocyte interaction under hypercholesterolemia using gene-targeted mice. Results: Lipidomic analysis in hypercholesterolemic mice showed that several lysophospholipids, including lysophosphatidic acid, accumulated in the lymphatic environment. Lysophosphatidic acid enables the potentiation of calpain systems in cultured LECs, which limits their ability to stabilize regulatory T cells (Treg) without altering Th1/Th2 (T helper type1/2) subsets. This occurs via the proteolytic degradation of MEKK1 (mitogen-activated protein kinase kinase kinase 1) and the subsequent inhibition of TGF (transforming growth factor)-β1 production in LECs. Targeting calpain systems in LECs expanded Tregs in the blood circulation and reduced aortic atherosclerosis in hypercholesterolemic mice, concomitant with the reduction of proinflammatory macrophages in the lesions. Treg expansion in the blood circulation and atheroprotection in calpain-targeted mice was prevented by the administration of TGF-β type-I receptor inhibitor. Moreover, lysophosphatidic acid-induced calpain overactivation potentiated the IL (interleukin)-18/NF-κB (nuclear factor κB)/VCAM1 (vascular cell adhesion molecule 1) axis in LECs, thereby inhibiting lymphocyte mobility on the cells. Indeed, VCAM1 in LECs was upregulated in hypercholesterolemic mice and human cases of coronary artery disease. Neutralization of VCAM1 or targeting LEC calpain systems recovered afferent Treg transportation via lymphatic vessels in mice. Conclusions: Calpain systems in LECs have a key role in controlling Treg stability and trafficking under hypercholesterolemia.